Moderate/High-Intensity Exercise and Coenzyme Q10 Supplementation May Reduce Tumstatin and Improve the Lipid Dynamics and Body Mass in Rats - Yasul, Yavuz; Akcinar, Faruk; Cinar, Vedat; Akbulut, Taner; Aydemir, Isa; Yalcin, Mehmet Hanifi; Aydin, Suleyman (Mdpi, 2025)
Coenzyme Q(10) (CoQ(10)) is a molecule that serves as a coenzyme for mitochondrial enzymes, playing a fundamental role in mitochondrial bioenergetics as an electron and proton carrier in the energy production process. This study aimed to examine the modulatory effects of moderate/high-intensity exercise and CoQ(10) supplementation on tumstatin, lipid dynamics, and body mass in rats. This study used 42 male Wistar Albino rats in six groups: a control group (C), a moderate-intensity continuous training group (MICT), a high-intensity continuous training group (HICT), a coenzyme Q(10) group (Q(10)), a moderate-intensity continuous training combined with Q(10) group (MICTQ(10)), and a high-intensity continuous training combined with Q(10) group (HICTQ(10)) to assess the effects of exercise and 5 mg/kg/daily CoQ(10) supplementation. Rats underwent treadmill training, and tumstatin levels in plasma, cardiac, and skeletal muscle tissues were measured using ELISA and immunostaining techniques. In addition to the plasma, high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), triglycerides (TG), and total cholesterol (TC) levels were analyzed using enzymatic methods, with the LDL-C calculated using the Friedewald equation. The atherogenic index of plasma was determined by the TG/HDL-C ratio. As compared to group C, body mass was significantly affected by both exercise intensity and supplementation (p = 0.01, eta(2) = 0.37), with the MICTQ(10) and HICTQ(10) groups demonstrating the greatest reductions by day 50th (p = 0.0003, d = 4.02; p = 0.0001, d = 3.99). Lipid profiles varied significantly between groups. Compared to the C group, the MICTQ(10) group exhibited the most substantial decreases in LDL-C (p = 0.03, d = 2.35) and TG levels (p = 0.03, d = 2.25), while the HICTQ(10) group showed the most pronounced reduction in TC levels (p = 0.001, d = 6.41). Regarding tumstatin levels, skeletal muscle tumstatin levels were lowest in the HICTQ(10) group (p = 0.01, d = 2.11). Moreover, cardiac muscle tumstatin levels were significantly lower in the MICTQ(10), MICT, and HICTQ(10) groups compared to in the C group (p = 0.004, d = 1.01). These findings suggest that both exercise intensity and CoQ(10) supplementation exert notable physiological effects, particularly in modulating body mass, lipid metabolism, and tumstatin levels.
Keywords: body mass; CoQ(10); Col-IV alpha 3; HICT; lipid; MICT; tumstatin